2011
DOI: 10.1038/ejhg.2011.212
|View full text |Cite
|
Sign up to set email alerts
|

Case report: type 1 diabetes in monozygotic quadruplets

Abstract: Type 1 diabetes (T1D) is an autoimmune disease characterized by the lack of insulin due to an autoimmune destruction of pancreatic beta cells. Here, we report a unique case of a family with naturally conceived quadruplets in which T1D was diagnosed in two quadruplets simultaneously. At the same time, the third quadruplet was diagnosed with the pre-diabetic stage. Remarkably, all four quadruplets were positive for anti-islet cell antibodies, GAD65 and IA-A2. Monozygotic status of the quadruplets was confirmed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
(51 reference statements)
1
11
0
Order By: Relevance
“…However, we believe that approximately ten subjects per group are sufficient to reveal genes with statistically significant alterations in their gene expression levels when high-density microarray chips are used. In this context and in many other aspects, the results of this study parallel our previous work [35] and the studies of other research teams in which microarray analyses obtained from a limited number of subjects provided highly relevant and statistically significant data [16, 3638]. Moreover, while our control group was not ideally age-matched to our other study groups, this variable produces negligible effects on our statistical analyses (data not shown) according to our comprehensive statistical analysis described elsewhere [35].…”
Section: Discussionsupporting
confidence: 83%
“…However, we believe that approximately ten subjects per group are sufficient to reveal genes with statistically significant alterations in their gene expression levels when high-density microarray chips are used. In this context and in many other aspects, the results of this study parallel our previous work [35] and the studies of other research teams in which microarray analyses obtained from a limited number of subjects provided highly relevant and statistically significant data [16, 3638]. Moreover, while our control group was not ideally age-matched to our other study groups, this variable produces negligible effects on our statistical analyses (data not shown) according to our comprehensive statistical analysis described elsewhere [35].…”
Section: Discussionsupporting
confidence: 83%
“…Beriou et al first reported an increased frequency of IL-9 + IL-17 + memory CD4 + T cells in subjects with type 1 diabetes mellitus (T1DM) [13]. In a subsequent study, gene expression analysis carried out on T1DM monozygotic quadruplets reconfirmed the involvement of IL-9 signaling in the pathogenesis of pancreatic β cell destruction [14]. However, whether the same holds good for type 2 diabetes mellitus (T2DM) is largely unknown.…”
Section: Resultsmentioning
confidence: 99%
“…It is also known that IL-17F is expressed earlier than IL-17A during Th17 cell development (38). A recent study showed that IL-9 signaling was associated with type 1 diabetes in two of monozygotic quadruplets (39). Increased numbers of TGF-b1-induced IL-9-secreting Th17 cells have been reported in type 1 diabetes, too (16).…”
Section: Discussionmentioning
confidence: 99%